Systematic review of costs and cost-effectiveness of treatment for relapsed/refractory acute leukemia in children and young adults. Issue 4 (3rd April 2022) - Soliman, Ranin; Heneghan, Carl; Bolous, Nancy S.; Sidhom, Iman; Ahmed, Sonia; Roberts, Nia; Oke, Jason; Elhaddad, Alaa
ABSTRACT: Introduction: Survival outcomes of children with relapsed/refractory (r/r) acute leukemia remain poor. Novel expensive treatments have been developed to improve their outcomes, yet, limited evidence exists about cost-effectiveness of alternative treatment strategies. Areas covered: A systematic review was conducted to summarize health-economic evidence about costs/cost-effectiveness of treating r/r acute leukemia in children/young adults. We searched Medline, Embase, and Cochrane databases until August 13th, 2021. Eligible articles included peer-reviewed original studies addressing r/r pediatric/young-adult acute lymphoblastic leukemia (ALL), and acute myeloid leukemia (AML). Quality assessment was conducted using Consolidated Health Economics Evaluation Reporting Standards (CHEERS) checklist. Expert Opinion: The majority of papers focused on CAR-T cell therapy, which is still a novel treatment for r/r ALL, and was found to be cost-effective, yet, there remain concerns over its long-term effectiveness, affordability, and equity in access. The next best treatment option is Blinatumomab, followed by Clofarabine therapy, whereas FLA-IDA salvage chemotherapy provides least value for money. The quality of evidence is moderate to high, with limited generalizability of findings due to high variability in outcomes obtained from modeling studies. Limited studies evaluated r/r AML. We provide recommendations to deliver cost-effective treatments in real-world contexts, with implications for healthcare policy and practice.